Developing the New Educational Paradigm in Russian Education - A. A. Verbitsky (Образование и наука)
The mission of education is changing according to the changing system of social values. Developed concepts related to the conformities of human growth determine the content, education and upbringing methods, pedagogic position and thinking, and way of life in educational institutions.The paper looks at the problems regarding the transition to the new educational paradigm. The author has conducted the historical review and retrospective analysis of the existing over the centuries educational paradigms: natural, civil, Christian, anthropological, and classical. The main emphasis is placed on the latter paradigm based on the principle of conformity to nature and learner’s perception and memorization of the ready-made educational material, since that out-of-date explanatory and illustrative traditional method still remains the most popular in pedagogic environment and dominating over the last three centuries in the world education. Lecture–workshop system of higher education appears to be its specific version based on the same theoretical principles. Most school teachers and academic staff at universities, colleges and vocational schools – some of them without special pedagogic education – work successfully according to Komensky, the founder of the class-lesson system of education. The comparison between the above mentioned classical paradigm and developing modern one in Russian educational system is given. The most significant contro- versies between the two educational models, preventing the implementation of the perspective innovations, are examined. It is emphasized that they can be solved on the theoretical and technological basis of the context teaching.